Cancer beyond organ and tissue specificity: Next‐generation‐sequencing gene mutation data reveal complex genetic similarities across major cancers. Issue 10 (17th April 2014) - Heim, D.; Budczies, J.; Stenzinger, A.; Treue, D.; Hufnagl, P.; Denkert, C.; Dietel, M.; Klauschen, F.
<x xml:space="preserve">Abstract</x> Cancer medicine relies on the paradigm that cancer is an organ‐ and tissue‐specific disease, which is the basis for classifying tumors. With the extensive genomic information now available on tumors it is possible to conduct analyses to reveal common genetic features across cancer types and to explore whether the established anatomy‐based tumor classification is actually reflected on the genetic level, which might provide important guides to new therapeutic directions. Here, we have conducted an extensive analysis of the genetic similarity of tumors from 14 major cancer entities using somatic mutation data from 4, 796 cases available through The Cancer Genome Atlas (TCGA) based on all available genes as well as different cancer‐related gene sets. Our analysis provides a systematic account of the genetic similarity network for major cancer types and shows that in about 43% of the cases on average, tumors of a particular anatomic site are genetically more similar to tumors from different organs and tissues (trans‐similarity) than to tumors of the same origin (self‐similarity). The observed similarities exist not only for carcinomas from different sites but are also present among neoplasms from different tissue origin, such as melanoma, acute myeloid leukemia, and glioblastoma. The current WHO cancer classification is therefore reflected on the genetic level by only about 57% of the tumors. These results provide a rationale to reconsider organ‐ and tissue‐specificity in cancer and contribute to the discussion about whether personalized therapies targeting specific genetic alterations may be transferred to cancers from other anatomic sites with similar genetic properties.